Enterprise architecture driven design of an artefact to support strategic Information Technology decision-making of Small Enterprises in Nigeria and South Africa - Alhassan, Mohammed (Department of Information Systems, 2018)
Information Technology (IT) is inevitably influencing the way enterprises operate, compete, and grow. The contemporary disruption has not excluded small companies. Small enterprises play a significant role in the growth of every economy but are hindered by limited skills, time, and money. The attributes of small enterprises influence the strategic and day-to-day operations. Small enterprise owners are often the managers who make the strategic decisions in order to solve specific problems. The decision style of small enterprise owner-managers limits the leveraging of IT. To ensure the sustainability of small enterprises in a contemporary business ecosystem, it is pertinent to strategise IT investment decisions. Enterprise architecture is a well-known approach to business and IT alignment. This study aimsto discover and develop how the complex enterprise architecture principles can strategise the IT decisionmaking process in small enterprises with limited resources and informal structures. The pragmatic philosophic stance was the premise for understanding the decision challenges and the development of a roadmap to intervene the problems the researcher identified. The Vaishnavi and Kuechler design science research methodology guided this study. The qualitative research approach was employed to collect verbal data with eleven small enterprise ownermanagers to understand the processes and the challenges of making IT decision in small enterprises. A thematic analysis of the findings revealed that lack of formalisation, limited information, and lack of IT skill created a critical bottleneck of IT investment decisions in small enterprises. An enterprise architecture-driven framework was developed to overcome the bounded rationality approach to IT choices in small enterprises. The framework holistically assesses organisational business-IT capabilities, constraints, and criteria to guide the decisionmaker's choice. The characteristics of small enterprises limit the successful implementation of the enterprise architecture-driven framework as a theoretical guideline for making optimal IT decisions in small enterprises. This study further developed an online IT decision-assistive tool informed by the framework. The instantiation artefact was demonstrated with six small enterprise owners from Nigeria and South Africa. The findings affirmed the prospect, potential, and relevance of an enterprise architecture-driven artefact as a tool to optimise strategic IT decisions in small manufacturing, service, and retail enterprises. The artefact developed in this study provided a practical intervention to the challenges of IT investment decisions in small enterprises.